THE INFLUENCE OF BRAND OFFERING AND BRAND EVALUATION ON CONSUMER PREFERENCE FOR LA REIA AND HARVEST IN SURABAYA AREA - Fransisca Fransisca (Perpustakaan Universitas Surabaya, 2016)
This research done to helps to explain non-price antecedents of consumer preference for cyber which is La Reia and extension brands which is Harvest that can influence on consumer preferences in Surabaya. Another objective of this research is to explore more about the relationship between brand offering, internet shopping experience, brand character, brand familiarity, brand evaluation, and brand for La Reia and Harvest Cake in Surabaya. This research is a quantitative research, and causal type research. In this research, the data was processed through Structural Equation Modelling (SEM) by using LISREL. This research uses sample characteristics which consumer who ever purchase in La Reia and Harvest Cake Surabaya through the website or social media minimum twice. The data is a primary data which obtained from the questionnaires which was distributed to 150 respondents. This research result indicated that Non-price antecedents have a significant influence towards consumer preference such as offering and evaluation of a web brands for La Reia and Harvest in Surabaya.